Some Biochemical Parameters in Congestive Heart Failure Patients in Baghdad City - Suha A. Al-Jowari (Journal of Global Pharma Technology, 2016)
The present study was designed to study the changes on some biochemical parameters in males with congestive heart failure (CHF). Ninety males with age ranges from (27-73) years have been involved in this study, divided into two groups; the first group involved 65 males with CHF and the second group involved 25 males without CHF from Teaching Baghdad Hospital. The patient's groups were divided according to their age into three groups (less than 40, 40-50 and more than 50 years). Blood samples were collected from each patient and control and used for analysis of renal function parameters, potassium, calcium and liver function. The results of the current study showed a highly significant (p < 0.01) increase in the concentration of blood urea, serum creatinine in HF patients as compared with the control group. While there is non-significant difference in the level of potassium in HF patients compared with the control group. Further, there was a highly significant (p < 0.01) decrease in concentration of calcium in patients group compare with the control. This study also illustrates a highly significant (p<0.01) increase in the liver function parameters which include alanine aminotransferase (ALT) and aspartate aminotransferases (AST) of HF patients compared with the control group. While there is non-significant difference in alkaline phosphatases (ALP) of HF patients compared with control group. There was also significant (P< 0.05) increase in total serum bilirubin (TSB) concentration of HF patients compared with the control group.Keywords: Congestive heart failure, Urea, Creatinine, ALT, AST, ALP, TSB.